Tracing Cognitive Struggles in EFL Writing: A Phenomenological Study of Language Errors among University Students - Fitriyani Bakri; Mardiyanah Nasta; Nur Mutmainnna Halim (PT. Global Research Collaboration, 2026)
Writing in EFL is a cognitively demanding activity involving idea generation, vocabulary retrieval, grammatical formulation, and self-monitoring. Nevertheless, studies on EFL writing errors have largely emphasized linguistic inaccuracies while giving limited attention to students’ cognitive and emotional experiences during writing production. This study aims to explore the cognitive struggles underlying language errors among Indonesian university students in an EFL writing context through a phenomenological perspective grounded in Levelt’s language production framework. This study employed a qualitative phenomenological design involving 24 students of Class A 2024, English Literature Study Program, Universitas Negeri Makassar who enrolled in Essay Writing class. Students were instructed to write a 1–2 paragraph research progress summary without using phones or digital references. Data were collected through students’ written texts, reflection journals, and stimulated recall interviews, and analyzed using thematic analysis informed by Interpretative Phenomenological Analysis (IPA). The findings reveal that students experienced difficulties in generating and organizing ideas, retrieving vocabulary, constructing sentences, and maintaining coherence. In addition, emotional factors such as confusion, nervousness, pressure, and cognitive fatigue intensified writing difficulties and interrupted writing fluency. The study demonstrates that language errors reflect deeper cognitive and emotional struggles during writing production rather than merely grammatical deficiencies.